Validation and reliability of a visualization and relaxation exercise program for enhancing speed climbing performance - Eduard Emor Kumenap; Fredrik Alfrets Makadada; Glady Sukma Perdana; Vlad Adrian Geantă; Ilham Ilham (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective: This study aimed to design, validate, and evaluate the reliability of a visualization and relaxation exercise program to improve speed climbing performance. While it may seem less popular, these techniques are crucial for creating more focus in the mind, decreasing anxiety, and improving motor skills in high-intensity sports. Methodology: In this research, a mixed-method research design was used with 30 athletes aged 18 – 35 from Yogyakarta state with a minimum of two years of climbing experience. Expert evaluations, observer training, and reliability testing were used in the validation process. Movement skill, power, balance, speed, timing, and tactical acumen are the criteria for assessment. Results: Aiken's V index scores (≥ 0.86) confirmed that the research instrument has content validity with strong agreement between the experts. High consistency was also reflected by observer reliability metrics, such as Cohen’s Kappa (≥ 0.86) and Kendall’s Tau B. The generalizability analysis of the instrument reinforced its accuracy and precision in measuring program impact. Conclusions: The manufactured program gives coaches and researchers a way of structuring mental training to improve speed climbing performance in a reliable framework. Its robust nature facilitates reliable measurement of athletes’ technical, tactical, and psychological attributes and, thus, the development of more effective training interventions. Additional research suggests utilizing this tool with diverse, larger populations and expanding the application to other precision-based sports.